(3HOGFY GdbQBfs - (3YHO GdYXje Hf YHO GdhGMO Hf XGaQ GdYOhGfj, GHf CHj GdGUHY,J (B654 (3g` s ((3GdeOQSI GdVjGHjI s)
(3ChdgG (B:s
(3cJGH HOjY GdbQBf GdPi gh JJeI ddEYLGR GdeJQLe HHjGf GdHQgGf CaQO Hg cJGH s
(3BNQgG (B:s
(3hEdMGb Pdc HgPG GdcJGH s
(3HChdg agQSs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B230s
Keywords: (3GdHdGZIs